Criminal risk assessment in Lithuania: current situation and future trends - ČĖSNIENĖ, ILONA; LAURINAVIČIUS, ALFREDAS; USTINAVIČIŪTĖ, LAURA (Kriminologijos studijos, 2015)
This paper examines the process of risk assessment of criminal behaviour in Lithuania. It addresses the presentation of risk assessment concepts, international and national trends in risk assessment procedures, and analysis of common characteristics of risk assessment instruments adapted in Lithuania. The paper comprises, first, a presentation of positive and statutory innovations related to risk assessment instruments approbation in Lithuania. The authors admit that the Lithuanian correctional system is following new trends of risk assessment. Contemporary and worldwide known risk instruments such as OASys, HCR-20, SVR-20, SARA, B-SAFER, PCL: SV were approved in Lithuania and put into practice. The use of these instruments enables practitioners to provide the scientific, evidence-based risk assessment that is necessary for effective offender punishment and risk management planning. It should be noted, that great attention is provided to risk assessment data reliability and validity to scientific research, thus assuring the qualification of assessors in Lithuania. Secondly, the paper describes difficulties encountered by specialists implementing penal and supervisory reforms. Mostly the discussion is concentrated on the problems related to the application of risk assessment instruments and the interpretation of assessment results in decision-making process related to the offender punishment peculiarities. Though the Lithuanian Justice system is implementing risk assessment as an obligatory procedure, however, recently it is mostly concentrated on the general risk assessment; the specified risk (e.g., sexual, violent) assessment is applied more rarely. In result, the specified risk assessment is not emphasised in the social research conclusions of parole. Accordingly, the parole commission and court representatives have no possibility to consider this type of information in making their decisions. The attention should also be directed to the practitioners’ work overload problems. The increasing number of criminals is related to the increasing demand of risk assessment procedures and risk management planning. However, the number of specialists working in this area and offenders that should be assessed is disproportionate. It leads to the constant work overload and turnover of qualified staff. Lastly, the paper presents recommendations for practitioners on how risk assessment and management practices and processes could be understood, and gives directions for a more proficient risk application of risk assessment instruments. It is obvious that cooperation between scientists and practitioners would lead to a more effective application of assessment instruments.